On the type specimens of Parazoanthus axinellae (Schmidt, 1862) (Hexacorallia: Zoanthidea) and its subspecies - Markovich, Annika; Bakran-Petricioli, Tatjana; Baltzinger, Elisabeth; Bruni, Michèle; Cenci, Elisa; Gunczy, Johanna; Meister, Marie; Ploner, Manuel; Swain, Audrey K.; Travaglini, Andrea; Swain, Timothy D. (Zootaxa, 2026)
Subspecies of Parazoanthus axinellae have been largely ignored since their inception and modern authors write of morphotypes rather than attempting to assign their specimens to these existing taxa. This hesitation to apply subspecies names is rooted in taxon definitions written to 19th century standards coupled with failure to designate type specimens that could be reexamined for clarification. Revealing the types or verifying that they no longer exist so that topotypes may be designated as neotypes creates a path for clarification of existing taxonomic hypotheses and discovering which modern morphotypes or cryptic taxa lay outside those circumscriptions. Here we reconstructed the history and updated the diagnoses of the types of P. axinellae and its nominal subspecies by reviewing historic scientific and archival documents, verifying type existence with their current caretakers, and reexamining their microanatomy. We identified type specimens and designated lectotypes and paralectotypes from the syntype series of Parazoanthus axinellae and subspecies axinellae, liguricus, and muelleri, redescribed them from histology of their type material, and provide diagnostic traits for identification in the field or laboratory. Type material for brevitentacularis was not recovered and permission to resample the type location has been denied.